2020
DOI: 10.1111/cxo.12958
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vision screening of 5–15‐year‐old children in three Tongan schools: comparison of The Auckland Optotypes and Lea symbols

Abstract: Background Comprehensive vision screening programmes for children are an important part of public health strategy, but do not exist in many countries, including Tonga. This project set out to assess: (1) the functional vision of children attending primary schools in Tonga and (2) how a new recognition acuity test (The Auckland Optotypes displayed on a tablet computer) compares to use of a standardised eye chart in this setting. Methods Children from three Tongan primary schools were invited to participate. Acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Good agreement was established between TAO and letter VA (Figure 2 a-c), indicating that TAO appears to be an equivalent measure to letter VA in children with amblyopia. The 95% LoA established in this study in the AE (±0.24 logMAR) and FE (±0.25 logMAR) were similar to, albeit slightly wider than, previously reported comparisons between TAO and logMAR letters in visually normal children (±0.20 logMAR) (7,8). The LoA observed in this study are also in line with those for well-established and widely used picture acuity charts.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Good agreement was established between TAO and letter VA (Figure 2 a-c), indicating that TAO appears to be an equivalent measure to letter VA in children with amblyopia. The 95% LoA established in this study in the AE (±0.24 logMAR) and FE (±0.25 logMAR) were similar to, albeit slightly wider than, previously reported comparisons between TAO and logMAR letters in visually normal children (±0.20 logMAR) (7,8). The LoA observed in this study are also in line with those for well-established and widely used picture acuity charts.…”
Section: Discussionsupporting
confidence: 89%
“…Existing evidence suggests that VA obtained with TAO is comparable to that obtained with ETDRS in adults. Similarly, strong agreement has been found between TAO and Sloan letters as well as Lea symbols in visually normal children (6)(7)(8). Such agreement is promising and suggests that TAO could enhance the accuracy of VA assessment in pre-literate children and potentially fulfil the criteria for a picture optotype test suitable for use in clinical trials.…”
Section: Introductionmentioning
confidence: 72%
“…Key health issues were identified for the children from the three primary schools surveyed in Tonga, including: physical health: oral health, ear health, overweight, injury, pain, respiratory conditions (including sore throat/RHD), gastrointestinal issues, skin conditions and non‐physical health: hardship related to access to sufficient supply of food, low health‐related quality of life and exposure to violence and abuse 22 . Encouragingly the exploratory study results showed the children had good functional vision 23 and described warm and loving family interactions.…”
Section: Successesmentioning
confidence: 99%